हिन्दी साहित्य को कँवलनयन कपूर की देन: Exploring the Significance of Kanhayan Kapoor in Hindi Literature and Society (Journal of Advances and Scholarly Researches in Allied Education, 2016)
साहित्यकार समाज का महत्वपूर्ण घटक होता है